The 2009-2010 Arctic polar stratospheric cloud season: a CALIPSO perspective - Pitts, M.C.; Poole, L.R.; Dörnbrack, A.; Thomason, L.W. (Atmospheric Chemistry and Physics, 2011)
Spaceborne lidar measurements from CALIPSO (Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observations) are used to provide a vortex-wide perspective of the 2009Ã¢ÂÂ2010 Arctic PSC (polar stratospheric cloud) season to complement more focused measurements from the European Union RECONCILE (reconciliation of essential process parameters for an enhanced predictability of Arctic stratospheric ozone loss and its climate interactions) field campaign. The 2009Ã¢ÂÂ2010 Arctic winter was unusually cold at stratospheric levels from mid-December 2009 until the end of January 2010, and was one of only a few winters from the past fifty-two years with synoptic-scale regions of temperatures below the frost point. More PSCs were observed by CALIPSO during the 2009Ã¢ÂÂ2010 Arctic winter than in the previous three Arctic seasons combined. In particular, there were significantly more observations of high number density NAT (nitric acid trihydrate) mixtures (referred to as Mix 2-enh) and ice PSCs. We found that the 2009Ã¢ÂÂ2010 season could roughly be divided into four periods with distinctly different PSC optical characteristics. The early season (15Ã¢ÂÂ 30 December 2009) was characterized by patchy, tenuous PSCs, primarily low number density liquid/NAT mixtures. No ice clouds were observed by CALIPSO during this early phase, suggesting that these early season NAT clouds were formed through a non-ice nucleation mechanism. The second phase of the season (31 December 2009Ã¢ÂÂ14 January 2010) was characterized by frequent mountain wave ice clouds that nucleated widespread NAT particles throughout the vortex, including Mix 2-enh. The third phase of the season (15Ã¢ÂÂ 21 January 2010) was characterized by synoptic-scale temperatures below the frost point which led to a rare outbreak of widespread ice clouds. The fourth phase of the season (22Ã¢ÂÂ28 January) was characterized by a major stratospheric warming that distorted the vortex, displacing the cold pool from the vortex center. This final phase was ...